Analyzing the Performance of Pakistan Equity Mutual Funds Using Multifactor Models: Pre-COVID Analysis - Danial, Muhammad; Iftikhar, Nadia; Shah, Syed Quaid Ali (Business Management and Strategy, 2023)
Previous literature has primarily focused on examining the determinants that impact mutual fund returns in developed and emerging economies. However, there is a dearth of empirical research on how multifactor models are associated with mutual fund returns in underdeveloped economies. The inconsistent literature regarding the efficiency of the literature posed a question of whether the fund managers can generate extra returns for the investors. To address this research gap, this study aims to analyze mutual fund returns using multifactor models, specifically the Capital Asset Pricing Model (CAPM), Fama-French three-factor model, Carhart four-factor model, Treynor-Mazuy and Fama Net-Selectivity. The first three models analyze the funds with four factors: market factor, growth factor, value factor and momentum factor. The results of the study indicate that the risk premium factor plays a crucial role in understanding mutual fund returns, as it exhibits significant value across all three models. However, the value and size factors were found to be insignificant in both the Fama-French and Carhart models. Additionally, the momentum factor was not significant in the Carhart model. Notably, the significant alpha observed in all multifactor models suggests the skill of mutual fund managers, which was further confirmed using the Treynor-Mazuy and Fama Net-Selectivity models to assess their timing and selectivity abilities in actively managed funds. Furthermore, the finding of the study suggests the inefficiency of the market. The investors could earn extra return from their investments. However, the managers play important role in generating the abnormal returns as suggested by Treynor-Mazuy and Fama Net-selectivity model significance. In addition to that, investors should consider the market risk premium in their investment returns.